Perencanaan Sumur Resapan Air Hujan di Masjid Al Mu’minin Kota Kendari - Lestari, Wahyu; Rosdiana, Rosdiana; Assiddieq, Moch. (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2022)
Development that does not pay attention to land use and long duration of rain with high intensity can make the houses of residents around the Al Mu’minin mosque flooded due to its low topography, so that infiltration wells are needed to reduce runoff. In this study, what was carried out was to plan the design of infiltration wells that can be used in the Al Mu’minin mosque based on the results of calculations for the rainfall intensity in the area of 28,60 mm/hour, runoff discharge of 4,92 m3/hour, the permeability value obtained was 8,00 cm/hour, so that the design size of the infiltration well design for a depth of 2 meters with a diameter of 1,8 meters. With this infiltration well, it is hoped that it will reduce runoff from rainwater that is inundated by being accommodated to increase the quantity of ground water.